2018
DOI: 10.1371/journal.pgen.1007277
|View full text |Cite
|
Sign up to set email alerts
|

Novel function of HATs and HDACs in homologous recombination through acetylation of human RAD52 at double-strand break sites

Abstract: The p300 and CBP histone acetyltransferases are recruited to DNA double-strand break (DSB) sites where they induce histone acetylation, thereby influencing the chromatin structure and DNA repair process. Whether p300/CBP at DSB sites also acetylate non-histone proteins, and how their acetylation affects DSB repair, remain unknown. Here we show that p300/CBP acetylate RAD52, a human homologous recombination (HR) DNA repair protein, at DSB sites. Using in vitro acetylated RAD52, we identified 13 potential acetyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 50 publications
(75 reference statements)
3
35
1
Order By: Relevance
“…Since nonhistone acetylation was first identified, increasingly more functions for acetylation have been found to act on various life processes, including DNA damage response and autophagy (Botrugno et al, 2012;Zhong et al, 2017;Yasuda et al, 2018), genomic stability (Billon et al, 2017;Fournier and Tora, 2017), transcriptional activity (Seo et al, 2015), protein degradation (Liu et al, 2013;Wei et al, 2018) and lysosomal function (Zhang et al, 2018). Previous studies have shown that acetylation could compete with ubiquitination at the same lysine residue, thus blocking the ubiquitin-mediated proteasomal degradation pathway to improve the protein stability, which is involved in cell cycle regulation (Lahusen et al, 2018), tumour suppression and progression (Wan et al, 2015;Choi et al, 2017), bacterial virulence (Sang et al, 2017) and signal transduction (Garcia-Aguilar et al, 2016;Beckwith et al, 2018;Wei et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Since nonhistone acetylation was first identified, increasingly more functions for acetylation have been found to act on various life processes, including DNA damage response and autophagy (Botrugno et al, 2012;Zhong et al, 2017;Yasuda et al, 2018), genomic stability (Billon et al, 2017;Fournier and Tora, 2017), transcriptional activity (Seo et al, 2015), protein degradation (Liu et al, 2013;Wei et al, 2018) and lysosomal function (Zhang et al, 2018). Previous studies have shown that acetylation could compete with ubiquitination at the same lysine residue, thus blocking the ubiquitin-mediated proteasomal degradation pathway to improve the protein stability, which is involved in cell cycle regulation (Lahusen et al, 2018), tumour suppression and progression (Wan et al, 2015;Choi et al, 2017), bacterial virulence (Sang et al, 2017) and signal transduction (Garcia-Aguilar et al, 2016;Beckwith et al, 2018;Wei et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the insertion of a long DNA fragment (more than 1.5 kb), the knock-in efficiency increased as the length of the homology arms increased, up to about 1500 bp [48]. Thus, long homology arms (more than 500 bp) are usually used for the knock-in of such a long DNA fragment [45,[49][50][51][52]. In this case, the knock-in is mediated by HR.…”
Section: Donor Dna Plasmid For Homology Directed Gene Knock-inmentioning
confidence: 99%
“…In this case, the knock-in is mediated by HR. The knock-in efficiency by HR is low [53], and accordingly, a selectable marker is introduced into the donor DNA plasmid for screening the knock-in clones in some cases [49][50][51][52]. Therefore, the selectable donor DNA plasmid for the HR-mediated gene knock-in contains left and right arms, the inserted gene of interest, and a selectable marker gene with promoter and transcription terminator regions.…”
Section: Donor Dna Plasmid For Homology Directed Gene Knock-inmentioning
confidence: 99%
“…Its RPA binding domains underlie RAD52´s biochemical functions in binding RPA-coated ssDNA, annealing, and homology-directed repair. Even though many details regarding the contribution of posttranslational modification to the function of RAD52 remain to be explored, we know that RAD52 acetylation is required for its accumulation at DSBs, sumoylation of yeast RAD52 for the choice of SSA over canonical recombination at repeats, and tyrosine phosphorylation of RAD52 for ssDNA, rather than dsDNA binding and the choice of SSA [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%